Pengelolaan Limbah Padat Bahan Berbahaya dan Beracun (B3) Medis RS Bhayangkara Tk. I Raden Said Sukanto - Clarisca, Vio Alma; Samadikun, Budi Prasetyo (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2020)
The hospital is one of the objects that has a major role in contributing medical waste, Â where the waste is classified as hazardous and toxic waste. Medical waste that not treated properly will bring nosocomial disease to humans and pollute the environment. For this reason, waste management is very needed. Medical waste produced by Bhayangkara Hospital Tk. I Raden Said Sukanto came from patient care rooms and medical support rooms. The amount of medical hazardous and toxic waste generated in January 2020 was 16.866 kg which included infectious, pharmaceutical, chemical and sharps waste. Medical hazardous and toxic solid waste management in Bhayangkara Tk. I Raden Said Sukanto Hospital includes reduction, packaging, symbol and labeling, storage, transportation, and processing. Bhayangkara Tk. I Raden Said Sukanto Hospital is guided by government regulations that forced in Indonesia. However, there was still some discrepancies between the existing conditions and regulations caused by the lack of adequate Human Resources.